Understanding the concept of career development among young cancer survivors in Malaysia - Musa, Siti Nur Syuhada; Hamzah, Siti Raba'ah (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
The purpose of this paper is to study on the understanding of the concept of career development among young working cancer survivors who were diagnosed with cancer during their childhood. This study was based on an extensive review of past researches on individual factors and career development among cancer survivors using the System Theory Framework. To conduct the literature reviews, the researcher utilized keywords such as career development, working life and young cancer survivors. From the literatures reviewed, the single factor that contributed to career development among young cancer survivors was the individual factor. Hence, addressing career development (the individual factor), might be important to improve employment outcomes for young cancer survivors. The importance and originality of this study were, it explored career development among young cancer survivors. This paper adopted elements from the System Theory Framework (STF) to derive the individual factor that influenced of career development. It is hoped this research findings will contribute to literatures on the significant factor contributing to career development among young cancer survivors in Malaysia.